Horticultural additives influence peat biogeochemistry and increase short-term CO2 production from peat - Bidhya Sharma; Tim R. Moore; Klaus-Holger Knorr; Henning Teickner; Peter M. J. Douglas; Nigel T. Roulet (Plant and Soil, 2024)
Aims Peat is used as a major ingredient of growing media in horticulture. Peat extracted from bogs can be acidic and low in nutrient availability and is therefore mixed with liming agents, nutrients, surfactants, perlite and so on. This study aims to estimate the rates at which raw peat and the modified peat (‘growing media’) decompose to release carbon dioxide (CO 2 ), to estimate the release of carbon (C) from liming agents and to estimate how peat biogeochemistry is changed. Methods We obtained 28 and 24 samples of raw peat and 24 growing media from four peat extraction companies in Canada. Growing media were treated with horticultural additives. We incubated the samples under laboratory conditions, measuring CO 2 production, tracer using $${\updelta }^{13}{\text{C}}$$ δ 13 C - $${{\text{CO}}}_{2}$$ CO 2 , pH, C, nitrogen (N) content and humification indices (HIs) from infrared technology called Fourier transform-mid infrared (FT-MIR). Results C:N ratio, pH, dissolved organic carbon, bulk density and C content differed significantly ( P < 0.05) between raw peats and growing media. There was more than a doubling of total $${{\text{CO}}}_{2}$$ CO 2 production from growing media compared to raw peat. HIs show higher values for the growing media, which could result from spectral band shifts in the growing media because of increased cation availability. $${\updelta }^{13}{\text{C}}$$ δ 13 C - $${{\text{CO}}}_{2}$$ CO 2 as a tracer showed an average 22% of the total $${{\text{CO}}}_{2}$$ CO 2 production orginated from added carbonate materials. Conclusion Our results provide the rates (0.15 ± 0.017mgCO 2 -Cg −1 d −1 ) at which horticultural peat decomposes and on the source of emitted $${{\text{CO}}}_{2}$$ CO 2 . This will improve current estimates CO 2 emissions from horticultural peat.